PENGARUH DISPLAY PRODUK, PROMOSI BELOW THE LINE, DAN EMOSI POSITIFTERHADAP KEPUTUSAN PEMBELIAN IMPULSIF (STUDI KASUS PADA HYPERMART BIG MALL DI KOTA SAMARINDA) - Elvia Fuji Harumi (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
ABSTRACT This study aimed to clarify the effect of display product, below the line promotion, and positive emotion to decision of purchasing of impulsif at consumer of Hypermart Big Mall Samarinda and know variable having an effect on dominant to decision of purchasing of impulsif conducted by consumer. As for analyzer the used is doubled linear analysis.Result of this research indicate that to be display product, promotion of below the line, and positive emotion have an effect on signifikan and simultan. Coefficient value of determinasi ( Square R) indicating that to be display product, promotion below the line, and positive emotion have influence to decision of purchasing of impulsif equal to 55,5%, while the rest 44,5% influenced by other variable of ang do not enter in this research. Keyword : display product, below the line promotion , and positive emotion, decision of purchasing of impulsif.